2020
DOI: 10.3390/nano10020231
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to UV Protection by Direct Surface Functionalization of TiO2 with the Antioxidant Polyphenol Dihydroxyphenyl Benzimidazole Carboxylic Acid

Abstract: Skin cancer is the most common malignant cancer with an incidence of 1 million cases/year. It is well known that exposure to UV radiation from sunlight leads the most frequent risk factors for several skin disorders including skin cancer. Sunscreen filters represent a valid protection against dangerous effects derived from UV radiation, and they can be divided in organic and inorganic UV filters. Adding, at the product formulation, molecules with booster effect, or also substances that can increase the protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Part of the UV radiation emitted by the sun is absorbed by oxygen molecules in the stratosphere (UVC, 100–290 nm), part is absorbed by the ozone layer (UVB, 290–320 nm), and the remainder of UVA radiation (UVA, 320–400 nm) and a small part of UVB are transmitted to the ground ( Battistin et al, 2020 ). Basking in the sun can help the conversion of 7-dehydrocholesterol into vitamin D in human skin, but long-term exposure to UV light causes mutagenic and non-specific damage to the epidermis.…”
Section: Sunscreenmentioning
confidence: 99%
“…Part of the UV radiation emitted by the sun is absorbed by oxygen molecules in the stratosphere (UVC, 100–290 nm), part is absorbed by the ozone layer (UVB, 290–320 nm), and the remainder of UVA radiation (UVA, 320–400 nm) and a small part of UVB are transmitted to the ground ( Battistin et al, 2020 ). Basking in the sun can help the conversion of 7-dehydrocholesterol into vitamin D in human skin, but long-term exposure to UV light causes mutagenic and non-specific damage to the epidermis.…”
Section: Sunscreenmentioning
confidence: 99%
“…The authors suggested the inclusion of these materials into sunscreen products [ 121 ]. In another study, coating of TiO 2 NPs with dihydroxyphenyl benzimidazole carboxylic acid (Oxisol) not only led to photolytic activity reduction, but also boosted its antioxidant effects and stabilization of the formulation [ 122 ]. By modifying the surface of TiO 2 NPs, it is also possible to improve the appearance of a sunscreen formulation, as formulations containing TiO 2 NPs modified with a complexing compound, p -toluene sulfonic acid, were found to be more transparent [ 123 ].…”
Section: Routes Of Exposure and Toxicity Of Tio 2 mentioning
confidence: 99%
“…In a typical high sun protection factor (SPF) sunscreen, the final concentration of PMFs and OCFs can reach 45% by weight [ 7 ]. In addition, UV boosters are used to further increase the SPF by physical effect, tuning the ratio between the UV shielding efficiency and the total UV filter concentration [ 8 ]. UV boosters are usually composed of plastic micro-sized spheres from petroleum origin, such as styrene/acrylate copolymers, that are well recognized as a waste in water pollution [ 9 ].…”
Section: Introductionmentioning
confidence: 99%